2009
DOI: 10.1037/a0017191
|View full text |Cite
|
Sign up to set email alerts
|

Myth and reality of the word caller: The relation between teacher nominations and prevalence among elementary school children.

Abstract: The purpose of the study was to investigate (a) the prevalence of word callers in elementary school, (b) the accuracy of teachers’ word caller nominations, and (c) teachers’ conceptualization of reading fluency and reading comprehension. To this end, 2 cross-sectional studies of second- and third- (N = 868) and of third- and fifth-grade (N = 202) children were conducted. Our findings suggest that word callers occur infrequently in the primary grades but that they are more prevalent in late elementary school. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 40 publications
3
23
0
1
Order By: Relevance
“…To justify their position, teachers sometimes invoke the existence of "word callers," students who supposedly read accurately but too quickly to be able to understand the text (Deno, 1985;Stanovich, 1986). Given that it has proven difficult to identify students fitting this profile (Hamilton & Shinn, 2003;Meisinger, Bradley, Schwanenflugel, Kuhn, & Morris, 2009), it would be tempting to dismiss these teachers' concerns as unfounded. As our findings suggest, however, they are probably correct to be concerned by students who read quickly and carelessly without considering punctuation, among other things.…”
Section: Characterizing Oral Readingmentioning
confidence: 96%
“…To justify their position, teachers sometimes invoke the existence of "word callers," students who supposedly read accurately but too quickly to be able to understand the text (Deno, 1985;Stanovich, 1986). Given that it has proven difficult to identify students fitting this profile (Hamilton & Shinn, 2003;Meisinger, Bradley, Schwanenflugel, Kuhn, & Morris, 2009), it would be tempting to dismiss these teachers' concerns as unfounded. As our findings suggest, however, they are probably correct to be concerned by students who read quickly and carelessly without considering punctuation, among other things.…”
Section: Characterizing Oral Readingmentioning
confidence: 96%
“…Students that fit this profile have been referred to as “word callers.” A word caller is a student who reads with adequate fluency but with limited comprehension; that is, a student can call out words in a text, but without fully understanding their meaning (Stanovich, 1986). However, few studies have examined the word caller phenomenon, and those that have been conducted provided mixed evidence regarding the existence of word callers and, if detected, their prevalence rates (Hamilton & Shinn, 2003; Meisinger, Bradley, Schwanenflugel, & Kuhn, 2010; Meisinger, Bradley, Schwanenflugel, Kuhn, & Morris, 2009).…”
Section: Word Callersmentioning
confidence: 99%
“…Variability and ambiguity of teacher definitions of the skills being assessed is likely to result in overestimation of their students' reading skills (Meisinger, Bradley, Schwanenfluegal, & Kuhn, ). Meisinger et al () found that when asked to nominate students as word callers, students who can “call out words” without understanding the text, there was a significant amount of inconsistency in both teachers understanding, and in the use of, the term. There was also a difference between how these teachers conceptualized reading fluency and reading comprehension, and how these skills were defined by the manufacturers of the assessment used (Meisinger et al, ).…”
Section: Variables That May Influence the Accuracy Of Teachers' Judgmmentioning
confidence: 99%
“…Meisinger et al () found that when asked to nominate students as word callers, students who can “call out words” without understanding the text, there was a significant amount of inconsistency in both teachers understanding, and in the use of, the term. There was also a difference between how these teachers conceptualized reading fluency and reading comprehension, and how these skills were defined by the manufacturers of the assessment used (Meisinger et al, ). Further, knowledge of the assessment used may also be an important factor.…”
Section: Variables That May Influence the Accuracy Of Teachers' Judgmmentioning
confidence: 99%